1998
DOI: 10.1002/(sici)1096-8652(199801)57:1<57::aid-ajh10>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Chronic relapsing thrombotic thrombocytopenic purpura: Role of therapy with cyclosporine

Abstract: Relapsing thrombotic thrombocytopenic purpura (TTP) is a rare disorder with most individuals experiencing 1 to 5 relapses. We report a patient with 18 episodes of thrombotic thrombocytopenic purpura (TTP), the highest number of relapses thus far described. The last 11 episodes were treated with regimens containing cyclosporine. The patient's medical record was reviewed for pertinent clinical, laboratory, and treatment data. We summarized various parameters for each episode and compared characteristics of relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Cyclosporine has been successfully used to treat refractory TTP in case reports and in a cohort study. [49][50][51][52][53] In a study evaluating the efficacy of PEX and cyclosporine in the treatment of TTP (included refractory TTP cases), remission was achieved in 89% of all patients. 53 Although this study also showed improvement in ADAMTS13 activity and in the suppression of ADAMTS13 inhibitors, the response rates were closely similar to those achieved with PEX alone.…”
Section: Cyclosporinementioning
confidence: 99%
“…Cyclosporine has been successfully used to treat refractory TTP in case reports and in a cohort study. [49][50][51][52][53] In a study evaluating the efficacy of PEX and cyclosporine in the treatment of TTP (included refractory TTP cases), remission was achieved in 89% of all patients. 53 Although this study also showed improvement in ADAMTS13 activity and in the suppression of ADAMTS13 inhibitors, the response rates were closely similar to those achieved with PEX alone.…”
Section: Cyclosporinementioning
confidence: 99%
“…As with rituximab, case reports have suggested the effectiveness of CSA in patients with relapsing or refractory forms of TTP [35][36][37][38][39][40][41]. These case reports suggest the effectiveness of CSA in patients who are refractory or resistant to PE.…”
Section: Ciclosporinmentioning
confidence: 99%
“…Single cases and small series have suggested that immunomodulatory drugs such as cyclosporine A, azathioprine, and mycophenolate mofetil could have benefit in the prevention of chronic relapses in acquired TTP [60][61][62]. However, the use of these drugs in this context requires further accurate evaluation through large studies.…”
Section: Other Immunomodulatory Drugsmentioning
confidence: 99%